Association between serum osteocalcin level and blood pressure in a Chinese population. (4th March 2018) - Xu, Yiting; Ma, Xiaojing; Xiong, Qin; Hu, Xiang; Zhang, Xueli; Yuan, Yeqing; Bao, Yuqian
Abstract: Purpose: This observational study investigated the association between serum osteocalcin level and blood pressure in a Chinese population. Materials and methods: A total of 2241 subjects (909 men and 1, 332 women; age, 24–78 years) from Shanghai communities were recruited. Subjects were divided into non-hypertensive and hypertensive groups according to diagnosis of hypertension based on the 1999 World Health Organization-International Society of Hypertension Guidelines. Serum osteocalcin levels were measured using an electrochemiluminescence immunoassay. Results: Men in the hypertensive group showed lower serum osteocalcin level compared with those in the non-hypertensive group, [16.37 (13.34–20.11) ng/mL versus 17.01 (14.23–20.79) ng/mL, p  = .039]. No difference in serum osteocalcin level was found between the two groups of women ( p  = .675). An inverse association was observed between serum osteocalcin level and systolic blood pressure (SBP) in men ( p  = .004), but serum osteocalcin level was not associated with diastolic blood pressure (DBP) in men ( p  = .472). No associations were detected between serum osteocalcin level and SBP or DBP in women (SBP: p  = .108; DBP: p  = .575). A multiple stepwise regression analysis showed an inverse association between serum osteocalcin level and SBP in men after adjusting for age, smoking status, family history of hypertension, and lipid and C-reactive protein levels (standardized β = –0.074, p  = .023), but the association disappeared after adjustment for body mass index, waist circumference, blood glucose, and homeostasis model assessment of insulin resistance ( p  = .327). Conclusions: Serum osteocalcin level was not independently associated with blood pressure in a Chinese population.